2020
DOI: 10.21325/jotags.2020.553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tourism Development Problems on Tourist Satisfaction and Revisit Intention: Example of Adıyaman

Abstract: The aim of the research is to determine the factors that affect the development of tourism in Adıyaman. In addition, it is aimed to reveal the impact of the factors affecting the development on the satisfaction of tourists and their intention to revisit. In the research, survey was used as a data collection tool. The local tourists visiting Adıyaman were focused on and 312 valid questionnaires were collected in total. Descriptive analyses, explanatory and confirmatory factor analyses, and structural equation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Even the negative perceptions of the residents on the socio-cultural environment from tourism might develop into the positive perceptions as well. In the literature, some research showed that there is a relationship between the positive perceptions of residents on the natural environment, the socio-cultural environment from tourism development and the benefits they received from tourism (Mansuroğlu, 2006;Martin et al, 2018;Arica and Ukav, 2020). Thus, the findings of this research are consistent with the literature mentioned above.…”
Section: Theoretical Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…Even the negative perceptions of the residents on the socio-cultural environment from tourism might develop into the positive perceptions as well. In the literature, some research showed that there is a relationship between the positive perceptions of residents on the natural environment, the socio-cultural environment from tourism development and the benefits they received from tourism (Mansuroğlu, 2006;Martin et al, 2018;Arica and Ukav, 2020). Thus, the findings of this research are consistent with the literature mentioned above.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…According to the theory of social change, residents influence the negative perceptions more into the positive perceptions when residents believe that the positive aspects of tourism will be more than the negative aspects of tourism. Thus, residents give their support for tourism development (Getz, 1994: 275;Arica and Ukav, 2020). With this view in hand, the primary requirement to develop the perceptions of residents toward tourism development is to take measures to increase the positive effects of tourism and to reduce the negative effects of tourism in the eyes of residents.…”
Section: Managerial Implicationsmentioning
confidence: 99%